Design assessment of waste water treatment facility for small scale mining Case study: Camgat Surong River in Didipio - Pramanagara, Rio Octovinary (Animo Repository, 2017)
Oceana Gold Philippines, Inc is a global gold mining company with strong presence in New Zealand, the Philippines, and the United States. In the Philippines, it is located in Didipio, Kasibu, Nueva Vizcaya. In Didipio, OceanaGold Philippines has to operate alongside active small scale mining that has been operating in the area for years. The effects of small scale mining operations are the high turbidty and total suspended solid of Camgat-Surong River which passes in OceanaGolds operation area. Due to the high turbidity and total suspended solid, direct flocculations was suggested as a treatment for the waste water from the small scale mining that affects Camgat-Surong River. During the OJT period, series of experiment involving sampling of the waste water, physicochemical characterization of waste water sample, treatment of the waste water, and total suspended solid test were done. Furthermore, flow rate, dosage of chemicals that will be used, and the dimension of the tank were taken into consideration for the possible design of the waste water treatment facility for small scale mining around OceanaGold Philippines, Inc. Initially, magnafloc 919, magnafloc 333, and ferric chloride were employed as flocculant and coagulant. The measurement of the flow rate was 0.682 m3/s and the dimension of the water tank was calculated to be 11.885 m. This was based that the shape of water treatment tank is cube so the length, width and height of the tank are the same for the design. The dosage test was conducted using 1L beaker glass and magnetic stirrer. It was found that 10 ppm of magnafloc 919 can effectively reduce turbidity and total suspended solid, thus improving the water quality parameter. 10 ppm of magnafloc919, gave the 92.005% removal for total suspended solid.